Descriptive Study of The Availability of Accessibility for Voters with Disabilities in The 2024 Elections in Jayapura City, Papua Province - Maling, Eram (GRAB KIDS: Journal of Special Education Need, 2025)
This research aims to analyze the accessibility of people with disabilities in the 2024 regional head election in the city of Jayapura, Papua Province. This research was studied using the dimensions of accessibility, accommodation, availability and acceptability. This research is a qualitative descriptive study using interview techniques and documentation to collect data. The research results show that the 2024 presidential election in Jayapura City has an accessibility dimension, there is the fact that the voting stations (TPS) provided by the organizers are not all easily accessible for people with disabilities, such as the existence of stairs which make it difficult for people with disabilities to enter the polling stations. The TPS entrance is narrow so access is difficult. There is no indication from the election organizers that there is a lack of accessibility for the visually impaired.  In the accommodation dimension, there are still TPS officer services that are not friendly to people with disabilities. Based on the availability dimension, there are constraints in the availability of materials, machines and methods so that it is not optimal in accommodating the rights of voters with disabilities. In the acceptability dimension, it is not yet friendly for people with disabilities, because there are still inaccurate perceptions of some people towards people with disabilities. General Election Organizers are advised to pay more attention to access for people with disabilities, especially regarding the affordability of polling stations, availability of facilities and infrastructure, availability of standard operating procedures (SOP) for people with disabilities, the skills and alertness of officers in handling voters with disabilities, as well as improving the way the public views them. people with disabilities. Keywords: Accessibility; Disability; General elections; Accommodation